2017
DOI: 10.1016/j.oraloncology.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional and cognitive impairment, social environment, frailty and adverse health outcomes in older patients with head and neck cancer, a systematic review

Abstract: Functional and cognitive impairment, depressive symptoms and social isolation are highly prevalent in head and neck cancer patients and associate with high risk of adverse health outcomes. In the future, these measurements may guide decision-making and customize treatments, but more research is needed to further improve and firmly establish clinical usability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 64 publications
4
53
1
Order By: Relevance
“…Although these studies represent a start to understanding frailty and outcomes in HNC surgery, there are limitations and gaps in the literature. A recent systematic review of longitudinal studies evaluating the association of functional or cognitive impairment, social environment, and/or frailty with adverse outcomes in patients with HNC failed to find any longitudinal studies assessing an association of frailty with adverse outcomes. Secondly, the median age of patients varied between studies, and many did not selectively include octogenarians and nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies represent a start to understanding frailty and outcomes in HNC surgery, there are limitations and gaps in the literature. A recent systematic review of longitudinal studies evaluating the association of functional or cognitive impairment, social environment, and/or frailty with adverse outcomes in patients with HNC failed to find any longitudinal studies assessing an association of frailty with adverse outcomes. Secondly, the median age of patients varied between studies, and many did not selectively include octogenarians and nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty has been defined as a syndrome of age‐related loss of physical, cognitive, social, and psychological functioning as well as the inability of the body to compensate for increased stress, which leads to decreased physiologic reserve across multiple organ systems . There are two main constructs for conceptualizing frailty: 1) the phenotypic model, and 2) the deficit accumulation measure of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…This difference was based on norms provided by the EORTC (http://groups.eortc.be/qol/manuals) with the threshold for statistical significance set at a p value of 0.05. Because of the severity of these patients’ pathology and the high risk of mortality of metastatic cancer combined with an aging population [6] and social isolation [2024, 25], we assumed that a potential 20% of patients will be lost to follow-up. These calculations showed that 320 patients are needed (160 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Survivors report numerous unmet physical, functional, psychosocial, and financial needs and problems with subsequent cancers, fatigue, pain, lymphedema, neuropathies, balance problems, mobility issues, bladder and bowel problems, dysphonia and other communication difficulties, dysphagia, cardiopulmonary and other end‐organ function declines, sexual dysfunction, depression and anxiety, and cognitive problems, among others . These problems can lead to reduced work productivity, quality of life, and survival . A confluence of several factors is limiting the resources of both health care systems and patients to offer and participate in needed follow‐up care services.…”
Section: The Need For Personalized Pathways For Cancer Follow‐up Carementioning
confidence: 99%
“…[8][9][10][11][12][13][14] These problems can lead to reduced work productivity, 15 quality of life, 16,17 and survival. [18][19][20][21][22] A conf luence of several factors is limiting the resources of both health care systems and patients to offer and participate in needed follow-up care services. These factors include: the growing number of survivors, especially those older than 65 years, who require the management of multiple comorbid conditions in addition to their cancer-specific concerns 2 ; health care provider shortages in oncology, primary care, and nursing [23][24][25][26] ; scarce provider education or training in how to provide cancer follow-up care, especially for the primary care workforce 27 ; and the increasing costs of cancer care 28 and posttreatment survivorship care.…”
mentioning
confidence: 99%